EFFECT OF EXTRACTION SOLVENTS AND DRYING CONDITIONS ON TOTAL POLYPHENOL CONTENT AND INDIVIDUAL PHENOLIC COMPOSITION OF ORANGE PEELS - relv (HUIT Journal of Science, 2025)
Although citrus peels are regarded as a byproduct of the juice production industry, they contain a high amount of bioactive compounds. This study aimed to evaluate the effects of different drying conditions (hot air oven) and extraction solvents (water, ethanol, methanol) on polyphenol content (TPC), phenolic composition (HPLC) in extracts from orange peels. The results showed that the water and methanol-to-water ratio of 1:1 presented the highest values for TPC in their extracts. Whereas, an ethanol-to-water ratio of 1:1 was found to be the best extracting solvent to get a higher yield of phenolic compounds (naringin and hesperidin). By comparing the drying conditions, the sample dried using a hot-air oven at 80 °C was the best temperature to retain polyphenolic content.